The challenge of reframing engineering education - Sale, Dennis (Springer Singapore Imprint: Springer, 2014)
The Challenge of Reframing Engineering Education is the first book to document the experience of implementing the CDIO Engineering Educational Framework in a large educational institution in the Asian context. It focuses on how to successfully implement and manage the key stages, activities and inevitable challenges that have to be negotiated in any large scale curriculum innovation. Its main purpose is to provide a practical resource for curriculum innovators and practitioners on what needs to be done, how and on what basis. It is written in a more narrative style than is typical of the genre, engaging the reader more intimately with the actual decision making processes and rationale that underpins curriculum innovation in the real context of institutional life. The book also encompasses many innovative practices for supporting student learning which are relevant in all mainstream educational contexts. These include an evidence-based learning approach for creative teaching, an explicit model for developing good thinking and a design framework for producing effective and efficient blended learning.